Kelembagaan Kelompok Usaha Bersama Nelayan Dalam Usaha Penangkapan Rajungan Di Kuala Teladas, Tulang Bawang - Santosa, Winarto; Hasani, Qadar; Supono, Supono; Damai, Abdullah Aman; Tresiana, Novita; Febryano, Indra Gumay (Universitas Bangka Belitung, 2025)
The Fishermen's Joint Business Group is a local institution that plays a vital role in sustainable blue swimming crab fishing practices. This study aims to analyze the institution structure of the Joint Business Group in supporting sustainable blue swimming crab fishing efforts in Kuala Teladas Village, Tulang Bawang Regency. This research is a qualitative study whose data collection was carried out through in-depth interviews, participant observation, and documentation study. Data were analyzed to examine the institution and organization structure of the group. The study results show that the Joint Business Group is vital as a collective forum for fishermen to discuss, share information, and access crab resources. The group's simple organization structure with clear rights, obligations, and sanctions in the Articles of Association/Bylaws encourages active participation by members. The implementation of blue swimming crab management policies has brought positive changes to fishermen's behaviour, especially in the use of environmentally friendly fishing gear. However, significant challenges include economic pressures during the lean season, lack of alternative livelihoods, and weak supervision. Increasing the institution capacity of Joint Business Groups is carried out through collaboration between non-governmental organizations, fisheries extension, and the government. This is implemented through socialization, training, and mentoring in organization management, leadership, and business diversification. Grant assistance and alternative business training for fishermen have strengthened the economic position of fishermen. Increasing institution capacity through collaboration with various stakeholders is key to supporting the socio-economic sustainability of fishermen and sustainable blue swimming crab fishing efforts.